2017
DOI: 10.3390/d9040054
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding of Environmental DNA Samples to Explore the Use of Uranium Mine Containment Ponds as a Water Source for Wildlife

Abstract: Understanding how anthropogenic impacts on the landscape affect wildlife requires a knowledge of community assemblages. Species surveys are the first step in assessing community structure, and recent molecular applications such as metabarcoding and environmental DNA analyses have been proposed as an additional and complementary wildlife survey method. Here, we test eDNA metabarcoding as a survey tool to examine the potential use of uranium mine containment ponds as water sources by wildlife. We tested samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Most studies that reported relative abundance (RAB) for this species used camera traps (n= 14), track and scat transects (n= 6), or track plots (n= 3). Hair snares (Downey et al 2007), observations by archery deer hunters (Cooper et al 2012), and environmental DNA (eDNA, Klymus et al 2017) were each reported detecting Grey Foxes by a single study.…”
Section: Abundancementioning
confidence: 99%
“…Most studies that reported relative abundance (RAB) for this species used camera traps (n= 14), track and scat transects (n= 6), or track plots (n= 3). Hair snares (Downey et al 2007), observations by archery deer hunters (Cooper et al 2012), and environmental DNA (eDNA, Klymus et al 2017) were each reported detecting Grey Foxes by a single study.…”
Section: Abundancementioning
confidence: 99%
“…This suggests that concentrated samples can contaminate negative controls during metabarcoding. Negative controls at each stage of metabarcoding can identify contaminant introduction (Klymus, Richter, Thompson, & Hinck, 2017;Ushio et al, 2017), but contaminants in these controls can amplify exponentially with no competition affecting inferences (Harper et al, 2018). Innovative approaches are needed to mitigate metabarcoding contamination, such as false positive estimation using occupancy models (Ficetola et al, 2015) or sequencing thresholds, i.e.…”
Section: Technical Pitfalls Of Edna Metabarcoding For Mammal Monitoringmentioning
confidence: 99%
“…Sun et al (2019) used eDNA metabarcoding to understand Dipteria and other organism populations in human caused roadside stormwater ponds. Additionally, Klymus et al (2017) examined how anthropogenic uranium containment ponds impacted the biodiversity of vertebrate species. Early applications also include monitoring of the re-introduction of Rhine sculpin (Cottus rhenanus) into its native range (Hempel et al, 2020) and at-risk, pre-restoration coral community monitoring (Nichols and Marko 2019).…”
Section: Introductionmentioning
confidence: 99%